2022
DOI: 10.1111/tbed.14446
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic of cutaneous fowlpox in a naïve population of chickens and turkeys in Austria: Detailed phylogenetic analysis indicates co‐evolution of fowlpox virus with reticuloendotheliosis virus

Abstract: Cutaneous fowlpox is a disease of chickens and turkeys caused by the fowlpox virus (FWPV), characterized by the development of proliferative lesions and scabs on unfeathered areas. FWPVs regularly carry an integrated, active copy of the reticuloendotheliosis virus (REV), and it has been hypothesized that such FWPVs are more problematic in the field. Extensive outbreaks are usually observed in tropical and sub‐tropical climates, where biting insects are more difficult to control. Here, we report an epidemic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Another limitation is that vaccine and field strains of FPV can be integrated with remnants of the reticuloendotheliosis virus (REV) long terminal repeats or the near full-length genome of REV [ 74 ]. Previous studies have shown that FPV vaccine contamination with REV caused tumors in the vaccinated birds [ 75 , 76 , 77 ], and the nearly intact integrated REV provirus could likely engender infectious REV, which, consequently, may lead to immunosuppression, thereby escalating the pathogenicity [ 77 , 78 ]. However, the mechanisms involved have not been fully elucidated [ 79 , 80 ].…”
Section: Various Important Virus Vectorsmentioning
confidence: 99%
“…Another limitation is that vaccine and field strains of FPV can be integrated with remnants of the reticuloendotheliosis virus (REV) long terminal repeats or the near full-length genome of REV [ 74 ]. Previous studies have shown that FPV vaccine contamination with REV caused tumors in the vaccinated birds [ 75 , 76 , 77 ], and the nearly intact integrated REV provirus could likely engender infectious REV, which, consequently, may lead to immunosuppression, thereby escalating the pathogenicity [ 77 , 78 ]. However, the mechanisms involved have not been fully elucidated [ 79 , 80 ].…”
Section: Various Important Virus Vectorsmentioning
confidence: 99%
“…Noteworthy is the implementation of multiplex PCR assays in i) detection of more than one pathogen in a course of a single PCR, or ii) for pathogen typing. Various assays for simultaneous detection of different pathogens have been described, such as protocols based on multiplex real-time PCR in detection of fowl poxvirus and reticuloenotheliosis virus [202,203] or detection of Mycoplasma gallisepticum and Mycoplasma synoviae [204] or conventional assays such as simultaneous detection of picorna-, astro-and caliciviruses [205] or Campylobacter, Arcobacter and Helicobacter species [206]. Similarly, diverse multiplex PCR assays are available for detecting and typing a pathogen within the same assay, and avian influenza viruses subjected to multiplex real-time PCR are a good example [207,208].…”
Section: Molecular Diagnosticsmentioning
confidence: 99%